Serial femtosecond X‐ray diffraction of 30S ribosomal subunit microcrystals in liquid suspension at ambient temperature using an X‐ray free‐electron laser. Issue 9 (30th August 2013) - Demirci, Hasan; Sierra, Raymond G.; Laksmono, Hartawan; Shoeman, Robert L.; Botha, Sabine; Barends, Thomas R. M.; Nass, Karol; Schlichting, Ilme; Doak, R. Bruce; Gati, Cornelius; Williams, Garth J.; Boutet, Sébastien; et al.
<x xml:space="preserve">Abstract</x> High‐resolution ribosome structures determined by X‐ray crystallography have provided important insights into the mechanism of translation. Such studies have thus far relied on large ribosome crystals kept at cryogenic temperatures to reduce radiation damage. Here, the application of serial femtosecond X‐ray crystallography (SFX) using an X‐ray free‐electron laser (XFEL) to obtain diffraction data from ribosome microcrystals in liquid suspension at ambient temperature is described. 30S ribosomal subunit microcrystals diffracted to beyond 6 Å resolution, demonstrating the feasibility of using SFX for ribosome structural studies. The ability to collect diffraction data at near‐physiological temperatures promises to provide fundamental insights into the structural dynamics of the ribosome and its functional complexes.